Species-specific influences of competition and tree size on drought sensitivity and resistance for three planted conifers in northern China - Rui Deng; Jinglei Liao; Tim Rademacher; Zhongqi Xu; Mingchao Du; Jianwei Zheng; Lihua Fu; Xianliang Zhang (Forest Ecosystems, 2025)
Droughts have caused tree growth decline and high tree mortality across temperate forests, however, how to manage planted forests to alleviate drought stress is still challenging. We used tree-ring and forest inventory data from different density stands to investigate how competition, tree diameter at breast height (DBH), tree age, and their interactions influence drought sensitivity and resistance for three widely-distributed and planted conifer species (Larix principis-rupprechtii, Picea meyeri, and Pinus sylvestris var. mongolica). Our results showed that the drought sensitivity of the three species was influenced by competition, tree size, and their interactions. Large L. principis-rupprechtii trees were particularly sensitive to drought during the growing season in medium to high-density stands, while the growth of large P. sylvestris var. mongolica was most affected by precipitation at low to medium density stands. Drought resistance of L. principis-rupprechtii trees decreased as tree size increased. Large L. principis-rupprechtii trees had lower drought resistance than small trees in all stands. Drought resistance of large P. meyeri trees exhibited high resistance to drought only in high-density stands. However, drought resistance of P. sylvestris var. mongolica trees was affected by tree size, competition, and their interactions. These results indicated that targeted silvicultural interventions, such as thinning, can be implemented to enhance drought resistance specifically for large L. principis-rupprechtii trees and small P. sylvestris var. mongolica trees in medium and high competition stands, and small P. meyeri trees in high competition stands. Our results highlight that properly conducted thinning can in some cases enhance growth resistance to droughts, depending on stand density, tree size, and tree species.